A successful intervention program for engineering students / Rafizah Kechil and Chew Yee Ming - Kechil, Rafizah; Chew, Yee Ming (Unit Penerbitan JSKM, 2024)
Further Differential Equations (MAT480) is a critical math course at the College of Engineering, Civil Engineering Studies, UiTM Cawangan Pulau Pinang. Unfortunately, during the October 2022-February 2023 semester, 30% of students failed this course. To address this, the "Boost Up Your Mathematical Skills Workshop (BMS)" was implemented for the March-August 2023 semester. The workshop sought to improve students’ mathematical skills and boost students' confidence in the subject. In the March-August 2023 semester, 91% of students successfully passed the course, indicating improved outcomes. In order to sustain this positive trend, the intervention program was implemented for the second time for students during the October 2023 – February 2024 semester, involving 26 students and two lecturers as facilitators. In this article, the studies aim to analyse the result of the pretest and posttest to forecast the student’s achievement in their final examination. If the forecast proves to be correct, then BMS will continue into upcoming semesters, enabling early performance assessment. Additional programs to raise performance can be implemented if the prognosis indicates a decline in student performance.